Complejo Gastronomico Municipal La 14 (2024)
The objective of this document is to design an architectural project called a gastronomic center for the city of Ibagué, located in the physical structure of Plaza de la 14, which, by restoring the heritage building and its immediate context, creating external support areas as a square for itinerant market and cultural events including new buildings, allow to establish the change of urban projection through the transformation of use.